Effect of structure factor on aggregate number concentration estimated using Rayleigh–Debye–Gans scattering theory - Lee, Jeonghoon (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
We suggest that the structure factor could be a source of uncertainty when the number concentration of non-absorbing aggregate particles is experimentally determined from Rayleigh–Debye–Gans (RDG) scattering theory. Different characteristics of various structure factors have been examined as a function of qRg. We present deviation of various structure factors from the exponential structure factor. Number concentrations estimated from various structure factors differ in the range of 1.0 < qRg < 10 where most of flame-synthesized non-absorbing particles are present as aggregates. We compare aggregate number concentrations of silica particles determined using various structure factors.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 519-525
Keywords: optyka; Rayleigh–Debye–Gans (RDG) scattering; aggregate particles; non-absorbing particles